PCR Test Juridical Review for Prospective Domestic Airplane Passengers - Hotmaria Hertawaty Sijabat; Sardjana Orba Manullang; Asep Saepullah; Karman Karman; Oskar Hutagaluh (IHSA Institute, 2022)
The mandatory Polymerase Chain Reaction (PCR) testing continues to be an interesting issue for many people. So the legality of the polymerase chain reaction test for local airline passengers is interesting for us to study. The data for this study were derived from secondary data from various journals and related literature readings that we obtained electronically. Then we explore as deeply as possible to understand the question and purpose of this study. So we also conducted a study through the evaluation system and data coding to draw valid conclusions and have high reliability. Sources of publication data include international and national journals. Based on the discussion of the findings, we can summarize that the regulatory status of mandatory testing for prospective passengers often changes, both in terms of price and legality, and other conditions. So along with this study, we report that there are still changes and the legal status of mandatory testing or not for prospective domestic passengers. It is hoped that this study will be helpful in the development of legal studies and business legality of PCR in Indonesia.